Perlindungan Hukum terhadap Korban Tindak Pidana Perdagangan Orang Terkait UU NO 21 Tahun 2007 - Nabila Restu Putri; Najwa Lathifa (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
Human trafficking constitutes a serious violation of human dignity and fundamental human rights, involving practices of exploitation that cause physical, psychological, and social harm to victims. In the perspective of Islamic law, such acts are categorized as jarimah because they contradict the principle of human honor (karāmah al-insān) as affirmed in Surah Al-Isra’ verse 70. Within the framework of Indonesian positive law, human trafficking is specifically regulated under Law Number 21 of 2007 on the Eradication of the Crime of Human Trafficking, which emphasizes not only the punishment of perpetrators but also the protection and recovery of victims. Using normative legal research through statutory and conceptual approaches, this article analyzes forms of legal protection provided to victims and examines obstacles in their implementation. The analysis shows that the law has regulated various victim rights, including confidentiality of identity, restitution, medical and social rehabilitation, repatriation, and social reintegration. However, implementation remains suboptimal due to limited institutional coordination, inadequate facilities and budgets, low public and law enforcement awareness, and the psychological trauma experienced by victims. Strengthening inter-agency coordination, improving the capacity of law enforcement officials, and adopting a victim-centered approach are necessary to ensure effective and comprehensive legal protection based on both Islamic legal principles and Indonesian positive law.